2009
DOI: 10.2807/ese.14.47.19417-en
|View full text |Cite
|
Sign up to set email alerts
|

Syphilis and gonorrhoea in men who have sex with men: a European overview

Abstract: w w w. e u ro s u rve i ll an c e . o rg 1 S u r v e i ll a n c e a n d o u t b r e a k r e p o r t s S y p h i l i S a n d g o n o r r h o e a i n m e n w h o h av e S e x w i t h m e n : a e u r o p e a n o v e r v i e w

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 29 publications
1
42
0
2
Order By: Relevance
“…6 In the United States in the past decade, this increase has particularly affected men who have sex with men (MSM) and, more recently, young African-Americans and Hispanics. 7,8 Similar trends for MSM have been observed throughout Europe 9 and China. 3,10,11 Some reports suggest that the increasing incidence of syphilis may be due to high-risk behaviours, such as methamphetamine use, 12-14 but as we will discuss later, the higher rates of syphilis and HIV coinfection may also be due to immunological factors.…”
Section: Syphilis Neurosyphilis and Hivsupporting
confidence: 60%
“…6 In the United States in the past decade, this increase has particularly affected men who have sex with men (MSM) and, more recently, young African-Americans and Hispanics. 7,8 Similar trends for MSM have been observed throughout Europe 9 and China. 3,10,11 Some reports suggest that the increasing incidence of syphilis may be due to high-risk behaviours, such as methamphetamine use, 12-14 but as we will discuss later, the higher rates of syphilis and HIV coinfection may also be due to immunological factors.…”
Section: Syphilis Neurosyphilis and Hivsupporting
confidence: 60%
“…In fact, HIV diagnoses among MSM in Western and Central Europe almost doubled in the last decade (Likatavicus et al, 2008), a resurgence that in many countries is linked to STIs (Dougan et al, 2007;Savage, Hughes, Ison, & Lowndes, 2009). Meta-analyses have confirmed that the presence of bacterial and viral STIs increase an individual's risk of both the acquisition and transmission of HIV infection (Ward & Rönn, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to WE countries, in Central and Eastern Europe between 1998 and 2007 there was a general decline in the number of reported syphilis cases (Savage et al, 2009). During the same period the sex ratio was relatively stable at around 1:1, with the exception of Slovenia where the male: female ratio rose to almost 5:1 in 2007 and 39% of male cases were reported to be MSM (Savage et al, 2009). Recent increases in overall early syphilis reported rates in Slovenia (in 2008 increase of 130% compared with 2007), with great majority of cases occurring in men (94%) and among cases in men a substantial proportion of cases among men known to have sex with men (44%) and among those almost one in three with a foreign MSM partner within three months preceding syphilis diagnosis, suggest recent increase in unsafe sexual behaviour among MSM and sexual mixing of Slovenian MSM with MSM abroad (Klavs et al, 2009).…”
Section: European Union and European Free Trade Association Countriesmentioning
confidence: 94%
“…It can be assumed that MSM to a larger extent choose to live in big cities since they assure more anonymity and less stigmatisation for MSM (Velicko et al, 2008). In contrast to WE countries, in Central and Eastern Europe between 1998 and 2007 there was a general decline in the number of reported syphilis cases (Savage et al, 2009). During the same period the sex ratio was relatively stable at around 1:1, with the exception of Slovenia where the male: female ratio rose to almost 5:1 in 2007 and 39% of male cases were reported to be MSM (Savage et al, 2009).…”
Section: European Union and European Free Trade Association Countriesmentioning
confidence: 99%